PENGARUH KUALITAS PELAYANAN, LOKASI DAN HARGA TERHADAP KEPUASAN KONSUMEN (Studi Kasus Pada Pesona Soccer Zone Futsal Joyogrand-Tlogomas) - Muhamad Ikhsomudin; Muhammad Hufron; Afi Rahmat Slamet (UNIVERSITAS ISLAM MALANG, 2017)
ABSTRACTThe research has a purpose to determine the effect of simultaneous andpartial quality of service, location and price to customer satisfaction, case studieson the charm Soccer Zone Futsal. So that can be know how the effect of servicequality, location and proce to customer satisfaction. The technique used isexplanatory research with the number of population 4320 consumers starting withMarch-April 2017 obtained by the number of samples as much as 95 respondents.The method used in this research is instrument test that is validity test andreliability test, normality test, clasiccal assumption test that multikolonierity test,and heterokedastisity test and hypothesis test that includes partial, simultaneoustest and dete coefisient.The result of this study indicate that 1) service quality has a significantpositive effect on customer satisfaction on the charm Soccer Zone Futsal, 2)location has a significant positive effect on customer satisfaction on the charmSoccer Zone Futsal, 3) price has a significant positive effect on customersatisfaction on the charm Soccer Zone Futsal.Keyword : Service Quality, Location, Price and Customer Satisfaction.